Hidden Political Agenda in Edward Albee’s The Goat, or Who is Sylvia? - Fatimah Ghaniem (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2019)
A case of zoophile, a sexual attraction toward animals, is considered rare to be talked within the scope of the queer theory. The wrong prejudices and discrimination received by zoophile also create a step backwards in getting acceptance from society compared to other sexual deviant orientation. As the issue keeps going, Edward Albee seizes his chance to shake the society’s mindset in reconsidering the deeds of zoophile through a drama entitled The Goat, or Who is Sylvia?. He creates a character named Martin, who lives as a zoophile differently from the preconceived notion of society raising a political interest to see a zoophile as a part of the society. This research attempts to investigate the political purposes behind the normalization of queerness in Martin’s character to reject intolerance and discrimination in society. The findings indicate that a political interest does exist from the presentation of Martin, which exhibits that a zoophile might have the same normal life as other people mostly do. This case of zoophile serves as an example of a minority case usually exposed to intolerance and discrimination. This research strongly argues that Albee tries to challenge the general perspective towards minority group in America, which sees them as aliens or a source of the plague. They can be anyone with a “normal” life; thus, they deserve equal treatment and not always to be considered as the others.